Relação planta-animal em pastagem de azevém (lolium multiflorum lam.) e milheto (pennisetum americanum (l.) leeke) com ovinos sob níveis de suplemento - Bremm, Carolina (2007)
This experiment was conducted aiming to elucidate aspects of the plant:animal interface through the ingestive behavior of sheep receiving different supplement levels (0; 0,5; 1,0 and 1,5% of live weight), kept on an Italian ryegrass (Lolium multiflorum Lam.) pasture during the winter period and Pearl millet (Pennisetum americanum (L.) Leeke) pasture on summer, under continuous variable stocking. The supplement utilized was a commercial ration. It was evaluated lactating ewes and ewe lambs when with their mothers and after weaning on Italian ryegrass pasture. On Pearl millet, the same ewe lambs were evaluated by experimental unit. The experimental design was completely randomized with repeated measures in time with four supplement levels and two area replicates. Supplement levels, with the structural characteristics of cold season pasture, influenced the ingestive behavior of ewes and ewe lambs (P<0.05). Supplement levels have not influenced (P>0.05) the bite size, being influenced by structure of cold season pasture and crude protein content of forage apparently consumed. On summer period, supplement levels and utilization periods of pasture altered the diurnal grazing, rumination and idling times (P<0.05).